The Influence Of Brand Image, Service Quality, And Store Atmosphere On The Decision To Purchase Arunda Coffee And Coffee Products Society In Sidoarjo - Ghora Wisnu Samudra,; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the effect of brand image, service quality, and store atmosphere on purchasing decisions. The population in this study were consumers of Arunda Coffee and Society Sidoarjo. The sampling technique for this study used accidental sampling. The type of data used in this study is quantitative data. The data collection technique in this study was a questionnaire. The data analysis test used validity test, reliability test, classical assumption test, multiple regression test, and t test.